2016
DOI: 10.1111/cei.12891
|View full text |Cite
|
Sign up to set email alerts
|

Association of NKG2D gene variants with susceptibility and severity of rheumatoid arthritis

Abstract: NKG2D (KLRK1) is a C-type lectin receptor present on natural killer (NK) cells, γδ, CD8 and CD4 T cells. Upon ligand binding, NKG2D mediates activatory and co-stimulatory signals to NK cells and activated CD4 T cells, respectively. Polymorphisms in NKG2D predispose to infectious diseases, cancer, transplantation and autoimmune disorders. We studied the influence of this NK receptor polymorphism on predisposition to and modification of the disease phenotype in patients with rheumatoid arthritis (RA). Eight diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 27 publications
2
25
1
1
Order By: Relevance
“…In joint diseases, NKG2DL were mainly investigated in RA. In line with previous reports [4] between OA and other arthritides. Interestingly, Rae1 appeared also upregulated in joints harvested from MSU crystals-injected mice, suggesting that cellular damage and /or activation following urate crystals-induced inflammation might respond to NKG2D / NKG2DLs cross talk, further supporting a regulatory role for NK or NKT cells in gout [19].…”
Section: Discussionsupporting
confidence: 93%
“…In joint diseases, NKG2DL were mainly investigated in RA. In line with previous reports [4] between OA and other arthritides. Interestingly, Rae1 appeared also upregulated in joints harvested from MSU crystals-injected mice, suggesting that cellular damage and /or activation following urate crystals-induced inflammation might respond to NKG2D / NKG2DLs cross talk, further supporting a regulatory role for NK or NKT cells in gout [19].…”
Section: Discussionsupporting
confidence: 93%
“…An up-regulation of inhibiting and stimulating NKG2 receptors was observed after allogeneic or autologous haematopoietic stem cell transplantation and in patients with rheumatoid arthritis, whereby a gene polymorphism of NKG2 was found to be associated with susceptibility and severity of rheumatoid arthritis [13][14][15]. Our focus was upon NK cells, NK T cells and T cells that produce IL-4 and/or TGF-b and/or co-express the inhibitory surface receptors CD158a (KIR2DL1), CD158b (KIR2DL2/L3), CD158e (KIR3DL1) and/or NKG2A and/or the stimulating receptor NKG2D.…”
Section: Introductionmentioning
confidence: 99%
“…Our focus was upon NK cells, NK T cells and T cells that produce IL-4 and/or TGF-b and/or co-express the inhibitory surface receptors CD158a (KIR2DL1), CD158b (KIR2DL2/L3), CD158e (KIR3DL1) and/or NKG2A and/or the stimulating receptor NKG2D. An up-regulation of inhibiting and stimulating NKG2 receptors was observed after allogeneic or autologous haematopoietic stem cell transplantation and in patients with rheumatoid arthritis, whereby a gene polymorphism of NKG2 was found to be associated with susceptibility and severity of rheumatoid arthritis [13][14][15]. Certain CD158 determinants summarized as killer cell immunoglobulin-like receptors (KIR) were found to be associated with RM [16][17][18][19] as well as control of viral infection, chronic rejection and graft loss in renal transplantation [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has found that specific SNPs in GWAS-identified susceptibility regions are associated with RA disease progression. For instance, certain SNPs in the interleukin ( IL ) -32 , NKG2D and vascular endothelial growth factor ( VEGF ) genes are known to contribute to the progression of RA 7 - 9 .…”
Section: Introductionmentioning
confidence: 99%